Antiangiogenic Effects of Eugenol in Chorioallantoic Membrane of Chick Embryo - K Kohestanian (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2015)
Introduction: Eugenol is a substance obtained from clove that has some therapeutic properties. Angiogenesis involves the formation of new blood vessels from the primary vessels. Since today natural products are taken into consideration in regard with anti-angiogenic therapies, this study intended to investigate anti-angiogenic effects of eugenol on chorioallantoic membrane (CAM) of chick embryo. Methods: In this experimental study, 70 Ross fertilized eggs were randomly divided into: control, sham and five experimental groups. On the 8th day of incubation, experimental groups were treated with 0.5 -5 mM of eugenol. On the 12th day, all cases were photographed and the numbers and lengths of vessels around the sponges were measured via applying image J software. Furthermore, the hemoglobin content was measured using Drabkin test, and then the embryo weight was recorded. The study data were analyzed statistically via SPSS software utilizing ANOVA test at significance level of p<0.05. Results: No significant difference was observed in regard with average number and length of vessels in sham and control groups. It is worth mentioning that the average number and length of vessels in experimental groups of 3, 4 and 5 revealed a significant decrease compared to the control group (p<0/001). The hemoglobin content of experimental groups of 2، 3, 4 and 5 demonstrated a significant decrease (p<0/001). Moreover, the weight of the embryos in 3, 4 and 5experimental groups showed a significant decrease compared to the controls (p<0.001). Conclusion: As the study findings revealed, Eugenol was reported to have inhibitory effect on angiogenesis in the chick embryo, therefore, it may be regarded as a good candidate for studies concerned with cancer treatment and pathological conditions associated with angiogenesis.